2014
DOI: 10.21608/aeji.2014.17201
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Hepcidin Level in Chronic Hepatitis C Virus Patients during Therapy

Abstract: The level of hepcidin in all cases was low before starting therapy and it showed a significant increase during the course of therapy. This rise was detected earlier in responding cases. A negative correlation was found between baseline hepcidin level and baseline viral load of the responding cases. Conclusion: Chronic HCV infection is associated with reduced level of serum hepcidin hormone. The reduced serum hepcidin in chronic HCV patients is fully reversible after IFN/RBV therapy. Initial rise in serum hepci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In order to compare Hep concentrations obtained in our study to the results of other authors we searched for studies that used the ELISA test for Hep determination. In the study investigating Hep concentration in patients with hepatitis C virus (HCV) infection, the authors reported median baseline Hep concentration of 75 pg/ml in the study group and 60 pg/ml in the control group [ 11 ]. The results obtained in our study were much higher than those obtained in patients with HCV or healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare Hep concentrations obtained in our study to the results of other authors we searched for studies that used the ELISA test for Hep determination. In the study investigating Hep concentration in patients with hepatitis C virus (HCV) infection, the authors reported median baseline Hep concentration of 75 pg/ml in the study group and 60 pg/ml in the control group [ 11 ]. The results obtained in our study were much higher than those obtained in patients with HCV or healthy controls.…”
Section: Discussionmentioning
confidence: 99%